Slump-retaining concrete glue reducing agent and preparation method thereof

By adopting a slump-containing concrete glue reducing agent containing polyolamine, ammonium acetate, sucrose and other components, the problem of poor mechanical properties of concrete caused by existing glue reducing agents is solved, and better fluidity, strength and durability are achieved.

CN119874252APending Publication Date: 2025-04-25HANGZHOU LIPING IND & TRADE CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510064046.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

When existing concrete glue reducing agents are applied to concrete, they lead to poor mechanical properties of concrete, affecting the construction and use effect.

Method used

A slump-conserving concrete glue reducing agent is used, including polyolamine solution, ammonium acetate solution, sucrose solution, triisopropanolamine solution, triethanolamine solution, sodium gluconate, water, industrial salt and molasses. Through the combination of these ingredients, the flowability, strength and durability of the concrete are improved.

Benefits of technology

This glue reducer can significantly improve the flowability and slump of concrete, enhance the early and later strength of concrete, improve construction performance and durability, and solve the problem of poor mechanical properties caused by existing glue reducers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005243717620000091
    Figure BDA0005243717620000091
Patent Text Reader

Abstract

The invention belongs to the technical field of concrete admixtures, and particularly discloses a slump-retaining concrete glue reducing agent and a preparation method thereof. The slump retaining type concrete glue reducing agent is prepared from the following raw materials in parts by weight: 90 to 100 parts of a polyalcohol amine solution, 120 to 130 parts of an ammonium acetate solution, 690 to 700 parts of a sucrose solution, 200 to 210 parts of a triisopropanolamine solution, 350 to 360 parts of a triethanolamine solution, 900 to 1000 parts of sodium gluconate, 1600 to 1700 parts of water, 210 to 220 parts of industrial salt and 80 to 90 parts of molasses. The slump-retaining concrete glue reducing agent prepared in the invention has relatively good strength, slump and fluidity, and the structural strength and stability of concrete are subsequently improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of concrete admixtures, and in particular to a collapse-preserving concrete adhesive reducer and a preparation method thereof. Background Art

[0002] Concrete is the largest building material in construction projects. Due to the accelerated urbanization process in recent years, the demand for commercial concrete has increased. Concrete is a composite material made of water, sand, stone and cement in a certain proportion. In the preparation process of concrete, a gel reducer is added to reduce the amount of cementitious materials. That is, under the same water-cement ratio, the amount of cementitious materials can be reduced appropriately to obtain better concrete working performance.

[0003] As a new generation of concrete admixture, concrete glue reducer can better improve the performance of concrete, increase the utilization rate of cement materials in concrete, reduce the amount of cementitious materials in concrete, and thus reduce cement production, which is in line with the environmental protection concept of green development and construction. In addition, on the basis of adding water reducer, concrete glue reducer can better exert its glue reducing performance.

[0004] In the prior art, the glue reducers mainly include sodium phenyl sulfonate, nitro acid, resin acid, etc., which can destroy the bonding force of the concrete surface, reduce the adhesion of the concrete surface and reduce the formation of cement binders, thereby improving the workability and fluidity of the concrete. However, these chemicals may interfere with the hydration process of cement particles, making it impossible for cement particles to fully exert their bonding force, thereby affecting the mechanical properties of concrete. Summary of the invention

[0005] In order to improve the problem that the existing adhesive reducer is used in concrete, resulting in poor mechanical properties of concrete, the present application provides a collapse-preserving concrete adhesive reducer and a preparation method thereof.

[0006] The present application provides a slump-preserving concrete adhesive reducer, which adopts the following technical solution: A slump-preserving concrete adhesive reducer comprises the following raw materials, measured by weight: 90-100 parts of a polyol amine solution, 120-130 parts of an ammonium acetate solution, 690-700 parts of a sucrose solution, 200-210 parts of a triisopropanolamine solution, 350-360 parts of a triethanolamine solution, 900-1000 parts of sodium gluconate, 1600-1700 parts of water, 210-220 parts of industrial salt and 80-90 parts of molasses.

[0007] By adopting the above technical solution, the polyolamine solution has a certain viscosity, which helps to improve the fluidity of concrete, increase the slump of concrete, and make concrete easier to construct, pour, vibrate and maintain; and the polyolamine solution promotes chemical reactions between materials during the hardening of concrete, increases the formation of cement gel, and improves the strength of concrete. Ammonium acetate solution can reduce the surface tension of water and reduce the bleeding phenomenon in concrete, thereby improving the fluidity of concrete mixture. Sucrose solution improves the fluidity of concrete by changing the surface tension of cement colloid and slowing down the interaction between particles in water, thereby reducing the difficulty of construction and improving the strength of concrete.

[0008] Triisopropanolamine solution can reduce the surface tension in concrete, reduce the adhesion and internal friction of concrete, and thus improve the fluidity of concrete. Triisopropanolamine can also increase the crack resistance of concrete, slow down the shrinkage rate of concrete, and thus reduce the possibility of cracks in concrete. Triethanolamine solution can promote the reaction between cement particles and water molecules, making cement more fully hydrated. Triethanolamine can promote the formation of more gels, increasing the density and strength of concrete. Sodium gluconate, as a plasticizer, has obvious auxiliary plasticizing effect and plastic preservation effect, improves the fluidity and plasticity of concrete, and makes concrete easier to operate and pour during construction.

[0009] Industrial salt has an antifreeze effect in concrete, allowing the concrete to hydrate normally in a low temperature environment and prevent freezing. At the same time, it can accelerate the coagulation and hardening process of concrete and improve the early strength of concrete. As an inhibitor, molasses can effectively slow down the rate of cement hydration reaction and control the formation of internal stress, thereby improving the strength and crack resistance of concrete and enhancing the long-term performance of concrete. The gel reducer prepared in this application ensures that the concrete maintains stable fluidity and workability during transportation, pouring and vibration, making the concrete easier to pour and compact.

[0010] Preferably, the mass ratio of the polyolamine solution, the ammonium acetate solution, the triisopropanolamine solution and the triethanolamine solution is 1:1.25-1.35:2.1-2.3:3.6-3.9.

[0011] By adopting the above technical scheme, the mass ratio of polyolamine solution, ammonium acetate solution, triisopropanolamine solution and triethanolamine solution is further limited within a certain range, and the polyolamine solution has good water solubility, and the solution has good viscosity, which helps to improve the fluidity and workability of concrete, and improves the density and strength of concrete. Ammonium acetate solution can reduce the bleeding phenomenon in concrete and improve the fluidity of concrete mixture. Triisopropanolamine prolongs the setting time of concrete, improves the construction performance of concrete, and may also improve the strength and durability of concrete by affecting the hydration process of cement. Triethanolamine can accelerate the hydration process of cement and improve the early strength of concrete. In addition, triethanolamine also has the effect of improving impermeability and density, and can enhance the durability and service life of concrete.

[0012] The thickening effect of polyolamine and the retarding effect of triisopropanolamine help improve the fluidity and workability of concrete, making it easier to pour and compact. The accelerated cement hydration effect of triethanolamine and the effect of triisopropanolamine on the cement hydration process may help improve the early strength and durability of concrete. At the same time, the thickening effect of polyolamine may also help improve the density and strength of concrete. The mixing of various components helps to extend the setting time of concrete, thereby improving the construction performance of concrete.

[0013] Preferably, the raw materials also include 60-70 parts of sodium sulphate.

[0014] By adopting the above technical solution, sodium sulfate can promote the hydration reaction of cement, accelerate the reaction of mineral components in cement clinker with water, generate more hydration products, and thus enhance the strength of concrete. At the same time, sodium sulfate can also fill the micropores in concrete, reduce the water permeability of concrete, and improve its durability. Sodium sulfate can react with the hydration products in concrete to form a porous cementitious material, thereby reducing the reaction between concrete and chemical substances in the external environment. This helps to improve the acid and alkali erosion resistance and salt erosion resistance of concrete and extend the service life of concrete.

[0015] Preferably, the pretreatment method of sodium sulphate comprises the following steps: (1) dispersing sodium sulphate in water, adding hexadecyltrimethoxysilane and citric acid, stirring for 20-25 minutes, filtering and drying to obtain sodium sulphate particles; (2) dispersing the modified diatomaceous earth in water, adding a silane coupling agent, stirring at a temperature of 60-65° C. for 1-1.5 h, filtering, and drying to obtain diatomaceous earth particles; (3) Dispersing the glauber salt particles of step (1) in water, adding the diatomaceous earth particles of step (2), ultrasonicating for 2-3 hours, adding hydroxypropyl methylcellulose, stirring at a temperature of 70-75° C. for 1-2 hours, and drying to obtain pretreated glauber salt.

[0016] By adopting the above technical scheme, the sodium sulfate is dispersed in water to form a uniform suspension. Hexadecyl trimethoxysilane has strong hydrophobicity and lipophilicity. Hexadecyl trimethoxysilane interacts with the surface of the sodium sulfate through its hydrophobic group to form an organic coating layer, which changes the surface properties of the sodium sulfate, making it more hydrophobic and lipophilic, enhancing the stability and dispersibility of the sodium sulfate particles, and preventing the particles from agglomerating and settling. Citric acid plays a role in adjusting the pH value of the system, enhancing the interaction between particles, and further enhancing the stability and performance of the sodium sulfate particles.

[0017] The modified diatomaceous earth is dispersed in water to form a uniform suspension. The ethoxy group in the silane coupling agent can react with the hydroxyl group on the surface of the diatomaceous earth to form a silicon-oxygen bond, thereby grafting the silane coupling agent to the surface of the diatomaceous earth, and subsequently enhancing the compatibility and adhesion of the diatomaceous earth with other materials.

[0018] The glauber salt particles are dispersed in water, diatomaceous earth particles are added, and then hydroxypropyl methylcellulose and hydroxypropyl methylcellulose are added. The diatomaceous earth particles have a porous structure and high adsorption. The glauber salt particles can be loaded on the surface of the diatomaceous earth particles. Hydroxypropyl methylcellulose has excellent adhesion, thickening and film-forming properties, so that the glauber salt particles and the diatomaceous earth particles are tightly bonded. Moreover, hydroxypropyl methylcellulose can form a sticky film, which is wrapped on the surface of the glauber salt particles and the diatomaceous earth particles to enhance the interaction between the particles. The obtained pretreated glauber salt has better dispersibility and stability, higher adsorption and catalytic activity, and improves the water retention and film-forming properties of the glauber salt.

[0019] Preferably, the mass ratio of the sodium sulphate, modified diatomaceous earth and hydroxypropyl methylcellulose is 1:0.6-0.7:0.1-0.2.

[0020] By adopting the above technical solution, the mass ratio of sodium sulfate, modified diatomite and hydroxypropyl methylcellulose is further limited within a certain range, and sodium sulfate can accelerate the initial and final setting time of concrete, improve the early strength of concrete, and improve the impermeability, frost resistance and durability of concrete. The porous structure of diatomite enables it to absorb and retain a large amount of water, form more gel with cement hydration products, fill the voids in concrete, reduce porosity, thereby enhancing the gelation of concrete and improving the density and strength of concrete. Hydroxypropyl methylcellulose can form a fiber mesh structure in concrete, increase the toughness and ductility of concrete, and thus improve the crack resistance of concrete.

[0021] Sodium sulfate can be loaded on the surface of diatomite particles, and hydroxypropyl methylcellulose can be wrapped on the surface of sodium sulfate particles and diatomite particles to enhance the interaction between particles. The drought-strengthening effect of sodium sulfate and the gelation effect of diatomite can accelerate the solidification and hardening process of concrete, thereby improving the early and late strength of concrete. The impermeability and frost resistance of sodium sulfate and the crack resistance of diatomite can jointly improve the durability of concrete and extend the service life of concrete.

[0022] Preferably, the ultrasonic frequency is 35-40kHz and the power is 1000-1200W.

[0023] By adopting the above technical scheme, the ultrasonic frequency and power are further limited, so that the alum powder particles and diatomaceous earth particles are evenly dispersed. The cavitation, stirring and micro-jet effects of the ultrasound are used to make the alum powder particles and diatomaceous earth particles vibrate, rub and collide violently in the water, which helps to break the agglomeration between the particles, improve the dispersion uniformity, promote the activation of the particle surface, and facilitate the subsequent treatment of the particles.

[0024] Preferably, the preparation method of the modified diatomaceous earth comprises the following steps: dispersing the diatomaceous earth in an oxalic acid solution, stirring for 30-35 minutes, then dispersing it in a sodium hydroxide solution, stirring for 45-50 minutes, washing it with water, then dispersing it in water, adding nano titanium dioxide, vitamin C and β-cyclodextrin, stirring evenly, and drying to obtain the modified diatomaceous earth.

[0025] By adopting the above technical solution, diatomaceous earth is mixed with oxalic acid to remove impurities and increase the porosity of the diatomaceous earth, and sodium hydroxide further removes impurities and can further clean impurities on the surface of the diatomaceous earth.

[0026] Nano-titanium dioxide has good mechanical properties, which can improve the compressive strength and tensile strength of concrete, making concrete more durable. Nano-titanium dioxide can be loaded in the pores of diatomaceous earth to improve the mechanical properties of diatomaceous earth. β-cyclodextrin is an oligosaccharide with a ring structure, which has excellent inclusion properties and stability. It can coat diatomaceous earth and nano-titanium dioxide, making diatomaceous earth and nano-titanium dioxide adhere tightly to form a more stable diatomaceous earth structure. Adding vitamin C can help promote the hydroxylation reaction on the surface of diatomaceous earth, change the adsorption performance and stability of diatomaceous earth, make diatomaceous earth and nano-titanium dioxide adsorb more closely, and subsequently increase the density of concrete.

[0027] Preferably, the mass ratio of the diatomaceous earth, nano-titanium dioxide and β-cyclodextrin is 1:0.4-0.5:0.2-0.3.

[0028] By adopting the above technical solution, the mass ratio of diatomite, nano-titanium dioxide and β-cyclodextrin is further limited within a certain range, and the modified diatomite obtained has good mechanical properties and adhesion. The microporous structure of diatomite helps to absorb and retain a certain amount of moisture, thereby improving the workability of concrete, making the concrete mixture easier to mix and construct; the microstructure of diatomite may help to enhance the impermeability and crack resistance of concrete, thereby improving the durability of concrete. The addition of nano-titanium dioxide can increase the compressive strength and tensile strength of concrete, making the concrete more durable. Nano-titanium dioxide can improve the frost resistance and corrosion resistance of concrete, further extending the service life of concrete. β-cyclodextrin is sticky and can coat diatomite and nano-titanium dioxide, so that diatomite and nano-titanium dioxide are tightly bonded to form a more stable diatomite structure.

[0029] The combined effect of diatomite, nano-titanium dioxide and β-cyclodextrin significantly improves the compressive strength, tensile strength, frost resistance and corrosion resistance of concrete. By improving workability, controlling slump loss and delaying cement hydration, concrete is easier to operate and control during mixing, transportation and pouring, which helps fill pores and cracks in concrete, thereby improving the density and impermeability of concrete.

[0030] In a second aspect, the present application also provides a method for preparing a collapse-preserving concrete adhesive reducer, comprising the following steps: (1) mixing a polyolamine solution, an ammonium acetate solution, a triisopropanolamine solution and a triethanolamine solution, and stirring them uniformly to obtain a mixed solution; (2) Mix sucrose solution, sodium gluconate, water, industrial salt and molasses, add the mixed solution of step (1), stir evenly, and obtain a slump-retaining concrete adhesive reducer.

[0031] By adopting the above technical scheme and the above preparation method, the operation is simple and the process time is short, which helps to improve the production efficiency of preparing the collapse-preserving concrete glue reducer. The obtained collapse-preserving concrete glue reducer has good mechanical properties and stability.

[0032] Preferably, the stirring temperature is 30-40°C and the time is 1-2h.

[0033] By adopting the above technical solution, the stirring temperature and time are further limited so that each component is mixed evenly, and the obtained concrete glue reducing agent has better comprehensive performance.

[0034] In summary, this application has the following beneficial effects: 1. The polyol amine solution in the present application has a certain viscosity, which helps to improve the fluidity of concrete, increase the slump of concrete, and make concrete easier to construct, pour, vibrate and maintain; the ammonium acetate solution can reduce the surface tension of water, reduce the bleeding phenomenon in concrete, and thus improve the fluidity of the concrete mixture.

[0035] 2. In the present application, the triisopropanolamine solution can reduce the surface tension in the concrete, reduce the adhesion and internal friction of the concrete, thereby improving the fluidity of the concrete; the triethanolamine solution can promote the reaction between cement particles and water molecules, making the cement more fully hydrated, and triethanolamine can promote the formation of more gels, thereby increasing the density and strength of the concrete.

[0036] 3. In the present application, sodium sulfate can promote the hydration reaction of cement, accelerate the reaction between the mineral components in the cement clinker and water, generate more hydration products, and thus enhance the strength of the concrete; sodium sulfate can also fill the micro pores in the concrete, reduce the water permeability of the concrete, and improve its durability. DETAILED DESCRIPTION

[0037] The present application is further described in detail below with reference to the embodiments.

[0038] The raw materials used in the examples and comparative examples can all be obtained commercially.

[0039] Preparation example of glauber powder Preparation Example 1-1 The pretreatment method of sodium sulphate comprises the following steps: (1) Disperse 100 kg of sodium sulphate in 120 L of water, add 10 kg of hexadecyltrimethoxysilane and 20 kg of citric acid, stir for 25 min, filter and dry to obtain sodium sulphate granules; (2) dispersing the modified diatomaceous earth in 90 L of water, adding 5 kg of silane coupling agent KH-550, stirring at 65 ° C for 1.5 h, filtering and drying to obtain diatomaceous earth particles; (3) Disperse the glauber salt particles of step (1) in 200 L of water, add the diatomaceous earth particles of step (2), ultrasonicate for 3 h, add hydroxypropyl methylcellulose, stir at 75 ° C for 2 h, and dry to obtain pretreated glauber salt.

[0040] The mass ratio of sodium sulphate, modified diatomaceous earth and hydroxypropyl methylcellulose is 1:0.6:0.2.

[0041] The ultrasonic frequency is 38kHz and the power is 1100W.

[0042] The preparation method of modified diatomite comprises the following steps: dispersing 90 kg of diatomite in 120 L of oxalic acid solution with a mass fraction of 10%, stirring for 35 minutes, then dispersing in 110 L of sodium hydroxide solution with a mass fraction of 12%, stirring for 50 minutes, washing with water, then dispersing in 130 L of water, adding nano titanium dioxide, 15 kg of vitamin C and beta-cyclodextrin, stirring evenly, and drying to obtain modified diatomite.

[0043] The mass ratio of diatomaceous earth, nano-titanium dioxide and β-cyclodextrin is 1:0.4:0.3.

[0044] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), no modified diatomaceous earth is added.

[0045] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (3), hydroxypropyl methylcellulose is not added.

[0046] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of sodium sulphate, modified diatomaceous earth and hydroxypropyl methylcellulose is 1:0.7:0.1.

[0047] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of sodium sulphate, modified diatomaceous earth and hydroxypropyl methylcellulose is 1:0.1:0.8.

[0048] Preparation Example 1-6 The difference from Preparation Example 1-1 is that in the preparation method of modified diatomite, no nano titanium dioxide is added.

[0049] Preparation Example 1-7 The difference from Preparation Example 1-1 is that β-cyclodextrin is not added in the preparation method of the modified Rongalite.

[0050] Preparation Example 1-8 The difference from Preparation Example 1-1 is that the mass ratio of diatomaceous earth, nano-titanium dioxide and β-cyclodextrin is 1:0.5:0.2.

[0051] Preparation Example 1-9 The difference from Preparation Example 1-1 is that the mass ratio of diatomaceous earth, nano-titanium dioxide and β-cyclodextrin is 1:0.05:0.65. Example

[0052] Example 1 A slump-preserving concrete adhesive reducer comprises the following raw materials by weight: 90 kg of a polyolamine solution, 130 kg of an ammonium acetate solution, 690 kg of a sucrose solution (sucrose is dissolved in water to obtain a sucrose solution with a solution concentration of 84%), 200 kg of a triisopropanolamine solution, 360 kg of a triethanolamine solution, 1000 kg of sodium gluconate, 1600 kg of water, 210 kg of an industrial salt, and 80 kg of molasses; the industrial salt is sodium chloride, the polyolamine is a polymerized alcoholamine with a concentration of 75% in liquid form, purchased from Wuhan Jiyesheng Chemical Co., Ltd.; the ammonium acetate solution is in liquid form, purchased from Hubei Xinghengye Technology Co., Ltd.; the triisopropanolamine solution is in liquid form, purchased from Shanghai Nanmu Chemical Co., Ltd.; the triethanolamine solution is in liquid form, purchased from Xingtai Xinlanxing Technology Co., Ltd.; and the molasses is purchased from Jinan Chenxuan Chemical Co., Ltd.

[0053] The preparation method of the collapse-preserving concrete adhesive reducer comprises the following steps: (1) mixing a polyolamine solution, an ammonium acetate solution, a triisopropanolamine solution and a triethanolamine solution, and stirring the mixture to obtain a mixed solution; (2) Mix sucrose solution, sodium gluconate, water, industrial salt and molasses, add the mixed solution of step (1), stir evenly, and obtain a slump-retaining concrete adhesive reducer.

[0054] The stirring temperature was 35°C and the stirring time was 2h.

[0055] Example 2 A slump-preserving concrete adhesive reducer, which differs from Example 1 in that it comprises the following raw materials, by weight: 100 kg of polyol amine solution, 120 kg of ammonium acetate solution, 700 kg of sucrose solution, 210 kg of triisopropanolamine solution, 350 kg of triethanolamine solution, 900 kg of sodium gluconate, 1700 kg of water, 220 kg of industrial salt, and 90 kg of molasses.

[0056] Example 3 A slump-preserving concrete adhesive reducer, which differs from Example 1 in that the mass ratio of the polyolamine solution, the ammonium acetate solution, the triisopropanolamine solution and the triethanolamine solution is 1:1.25:2.1:3.6.

[0057] Example 4 A slump-preserving concrete adhesive reducer, which differs from Example 1 in that the mass ratio of the polyolamine solution, the ammonium acetate solution, the triisopropanolamine solution and the triethanolamine solution is 1:1.35:2.3:3.9.

[0058] Example 5 A slump-preserving concrete adhesive reducer, which differs from Example 1 in that the raw materials further include 60 kg of sodium sulphate purchased from Yingcheng Xiangfa Chemical Co., Ltd.

[0059] Example 6 A collapse-preserving concrete adhesive reducer, which differs from Example 5 in that the raw materials further include 70 kg of sodium sulphate.

[0060] Example 7 A collapse-preserving concrete adhesive reducer, which is different from Example 5 in that the sodium sulfate is prepared using Preparation Example 1-1.

[0061] Example 8 A collapse-preserving concrete adhesive reducer, which is different from Example 7 in that the sodium sulfate is prepared using Preparation Example 1-2.

[0062] Example 9 A collapse-preserving concrete adhesive reducer, which is different from Example 7 in that the sodium sulfate is prepared using Preparation Example 1-3.

[0063] Example 10 A collapse-preserving concrete adhesive reducer, which is different from Example 7 in that the sodium sulfate is prepared using Preparation Example 1-4.

[0064] Embodiment 11 A collapse-preserving concrete adhesive reducer, which is different from Example 7 in that the sodium sulfate is prepared using Preparation Example 1-5.

[0065] Example 12 A collapse-preserving concrete adhesive reducer is disclosed, which differs from Example 7 in that glauber salt is prepared using Preparation Example 1-6.

[0066] Embodiment 13 A collapse-preserving concrete adhesive reducer, which is different from Example 7 in that the sodium sulfate is prepared using Preparation Example 1-7.

[0067] Embodiment 14 A collapse-preserving concrete adhesive reducer, which is different from Example 7 in that the sodium sulfate is prepared using Preparation Examples 1-8.

[0068] Embodiment 15 A collapse-preserving concrete adhesive reducer, which is different from Example 7 in that the sodium sulfate is prepared using Preparation Examples 1-9.

[0069] Comparative Example Comparative Example 1 A slump-preserving concrete adhesive reducer is different from Example 1 in that no polyol amine solution is added, but an equal amount of water is used instead.

[0070] Comparative Example 2 A slump-preserving concrete adhesive reducer, which differs from Example 1 in that ammonium acetate solution is not added, but an equal amount of water is used instead.

[0071] Comparative Example 3 A slump-preserving concrete adhesive reducer is different from Example 1 in that triisopropanolamine solution is not added and an equal amount of water is used instead.

[0072] Comparative Example 4 A slump-preserving concrete adhesive reducer is different from Example 1 in that no triethanolamine solution is added, and an equal amount of water is used instead.

[0073] Performance testing The performance of the slump-preserving concrete adhesive reducer prepared in Examples 1-15 and Comparative Examples 1-4 was tested. The test was conducted in accordance with the JC / T 2469-2018 "Concrete Glue Reducer" standard, and the concrete slump and water seepage rate test was conducted in accordance with the GB / T 50080-2016 "Standard for Performance Test Methods of Ordinary Concrete Mixtures". The mix ratio of the water seepage test adopted the concrete mix ratio of high-performance water reducer in GB 8076-2008 "Concrete Admixtures", and the slump was controlled to be (210±10) mm. The concrete mix ratio was: m(cement): m(sand): m(stone) = 350:735:1115, the water consumption was adjusted according to the slump control value, and the amount of glue reducer added was 0.6% (relative to the amount of cementitious material). The test results are shown in Table 1.

[0074] Table 1 Test data of embodiments and comparative examples As can be seen from Table 1, the concrete adhesive reducer prepared in Examples 1-2 of the present application has good mechanical properties, adhesive reduction rate, water bleeding rate and mechanical strength. Among them, the 7d compressive strength of Example 1 is 30.1MPa, the 28d compressive strength is 42.5MPa, the adhesive reduction rate is 7.2%, the slump 0h is 223mm, the 2h is 200mm, and the water bleeding rate is 2.4%, indicating that the prepared slump-preserving concrete adhesive reducer has good mechanical properties and mechanical strength, and the various components cooperate with each other, which not only improves the fluidity of the concrete, but also increases the strength and durability of the concrete.

[0075] Example 3-4 further defines the mass ratio between the polyolamine solution, ammonium acetate solution, triisopropanolamine solution and triethanolamine solution, and comparative examples 1-4 do not add polyolamine solution, ammonium acetate solution, triisopropanolamine solution and triethanolamine solution, respectively. As can be seen from Table 1, the test results of the compressive strength, slump, glue reduction rate and water bleeding rate of Examples 3-4 at 7d and 28d are significantly better than those of Examples 1-2, and the test results of the corresponding properties of Comparative Examples 1-4 are significantly worse than those of Examples 1-2, indicating that the mixing of polyolamine solution, ammonium acetate solution, triisopropanolamine solution and triethanolamine solution has a synergistic effect, which helps to prolong the setting time of concrete, thereby improving the construction performance of concrete.

[0076] Examples 5-6 added sodium sulphate purchased from the market. As can be seen from Table 1, the test results of 7d and 28d compressive strength, slump, glue reduction rate and water bleeding rate are significantly better than those of Examples 1-2, indicating that the addition of sodium sulphate can promote the hydration reaction of cement and generate more hydration products, thereby enhancing the strength of concrete. Sodium sulphate can also fill the micropores in concrete, reduce the water permeability of concrete, and improve its durability.

[0077] The glauber salt of Example 7 is prepared by the present application. As can be seen from Table 1, the test results of the compressive strength, slump, glue reduction rate and water bleeding rate at 7d and 28d are significantly better than those of Examples 5-6, indicating that the glauber salt prepared by the present application has better comprehensive performance, and the prepared glauber salt has better dispersibility and stability, higher adsorption and catalytic activity, which improves the water retention and film-forming properties of the glauber salt, and is subsequently applied to concrete to improve the comprehensive performance of the concrete.

[0078] In the preparation methods of sodium sulfate in Examples 8-9, modified diatomaceous earth and hydroxypropyl methylcellulose are not added respectively. In Examples 10-11, the mass ratio of sodium sulfate, modified diatomaceous earth and hydroxypropyl methylcellulose is changed. It can be seen from Table 1 that the test results of the compressive strength, slump, gel reduction rate and water bleeding rate of Examples 8-9 at 7d and 28d are significantly worse than those of Examples 7 and 10, but better than those of Examples 5-6. The test results of the corresponding properties of Example 11 are significantly better than those of Examples 8-9, but worse than those of Examples 7 and 10, indicating that sodium sulfate can be loaded on the surface of diatomaceous earth particles, hydroxypropyl methylcellulose can be wrapped on the surface of sodium sulfate particles and diatomaceous earth particles, and the interaction between particles is enhanced. The drought strength effect of sodium sulfate and the gelation effect of diatomaceous earth can accelerate the solidification and hardening process of concrete, thereby improving the strength of concrete and extending the service life of concrete.

[0079] In the preparation method of modified diatomite in Examples 12-13, nano titanium dioxide and β-cyclodextrin are not added respectively. In Examples 14-15, the mass ratio of diatomite, nano titanium dioxide and β-cyclodextrin is changed. As can be seen from Table 1, the test results of the compressive strength, slump, glue reduction rate and water bleeding rate of Examples 12-13 at 7d and 28d are significantly better than those of Example 8, but worse than those of Example 7 and Example 14. The test results of the corresponding properties of Example 15 are significantly better than those of Examples 12-13, but worse than those of Examples 7 and Example 14, indicating that the addition of nano titanium dioxide can improve the compressive strength and tensile strength of concrete, make concrete more durable, and extend the service life of concrete. β-cyclodextrin has viscosity and can coat diatomite and nano titanium dioxide, so that diatomite and nano titanium dioxide are tightly bonded to form a more stable diatomite structure, thereby improving the comprehensive performance of concrete.

[0080] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A slump-preserving concrete adhesive reducer, characterized in that: The invention comprises the following raw materials in parts by weight: 90-100 parts of polyolamine solution, 120-130 parts of ammonium acetate solution, 690-700 parts of sucrose solution, 200-210 parts of triisopropanolamine solution, 350-360 parts of triethanolamine solution, 900-1000 parts of sodium gluconate, 1600-1700 parts of water, 210-220 parts of industrial salt and 80-90 parts of molasses.

2. A slump-preserving concrete adhesive reducer according to claim 1, characterized in that: The mass ratio of the polyolamine solution, the ammonium acetate solution, the triisopropanolamine solution and the triethanolamine solution is 1:1.25-1.35:2.1-2.3:3.6-3.

9.

3. A slump-preserving concrete adhesive reducer according to claim 1, characterized in that: The raw materials also include 60-70 parts of sodium sulphate.

4. A slump-preserving concrete adhesive reducer according to claim 3, characterized in that: The pretreatment method of sodium sulphate comprises the following steps: (1) Disperse sodium sulphate in water, add hexadecyltrimethoxysilane and citric acid, stir for 20-25 minutes, filter and dry to obtain sodium sulphate granules; (2) dispersing the modified diatomaceous earth in water, adding a silane coupling agent, stirring at a temperature of 60-65° C. for 1-1.5 h, filtering, and drying to obtain diatomaceous earth particles; (3) Dispersing the glauber salt particles of step (1) in water, adding the diatomaceous earth particles of step (2), ultrasonicating for 2-3 hours, adding hydroxypropyl methylcellulose, stirring at a temperature of 70-75° C. for 1-2 hours, and drying to obtain pretreated glauber salt.

5. A slump-preserving concrete adhesive reducer according to claim 4, characterized in that: The mass ratio of the sodium sulphate, modified diatomaceous earth and hydroxypropyl methylcellulose is 1:0.6-0.7:0.1-0.

2.

6. A slump-preserving concrete adhesive reducer according to claim 4, characterized in that: The ultrasonic wave has a frequency of 35-40 kHz and a power of 1000-1200 W.

7. A slump-preserving concrete adhesive reducer according to claim 4, characterized in that: The preparation method of the modified diatomite comprises the following steps: dispersing the diatomite in an oxalic acid solution, stirring for 30-35 minutes, then dispersing it in a sodium hydroxide solution, stirring for 45-50 minutes, washing it with water, then dispersing it in water, adding nano titanium dioxide, vitamin C and beta-cyclodextrin, stirring evenly, and drying to obtain the modified diatomite.

8. A slump-preserving concrete adhesive reducer according to claim 7, characterized in that: The mass ratio of the diatomaceous earth, nano titanium dioxide and beta-cyclodextrin is 1:0.4-0.5:0.2-0.

3.

9. The method for preparing a slump-preserving concrete adhesive reducer according to claim 1, characterized in that: The steps include: (1) Mixing a polyolamine solution, an ammonium acetate solution, a triisopropanolamine solution and a triethanolamine solution, stirring the mixture to obtain a mixed solution; (2) Mix sucrose solution, sodium gluconate, water, industrial salt and molasses, add the mixed solution of step (1), and stir evenly to obtain a slump-retaining concrete adhesive reducer.

10. The method for preparing a collapse-preserving concrete adhesive reducer according to claim 9, characterized in that: The stirring temperature is 30-40°C and the stirring time is 1-2h.

Citation Information

Cited By

  • Enhanced concrete water-retaining slurry-improving agent and preparation method thereof

    CN121872701A